2013
DOI: 10.15332/s1794-9998.2013.0002.12
|View full text |Cite
|
Sign up to set email alerts
|

Escala de soporte social de Tagaya, Okuno, Tamura y Davis: propiedades psicométricas en adultos mayores

Abstract: Resumenconducida en cuatro muestras independientes de adultos mayores de la Ciudad de México. La escala, -cial mediante un solo factor que explica el 60,7% de soledad. Con base en ello, se concluye que la ESS-AM -nes de tamizaje para evaluar si el adulto mayor cuenta con adecuados niveles de apoyo social percibido. Palabras clave:ledad, escala. AbstractThis research presents the Spanish adaptation and validation of the Social Support Scale (ESS-AM) from in four independent samples of elderly people from Mexico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It is important to comment that of the eight items that were eliminated to achieve a better fit and greater discrimination capacity of the model proposed by Lasher and Faulkender,items 2,4,5,6 and 16 were also eliminated by Rivera-Ledesma et al (2007) and Ornelas, Gastélum, Lopez-Walle, et al (2016) in their studies on the factor structure of the Lasher and Faulkender's Anxiety about Aging Scale in a Mexican population, while these same items in other studies with a non-Mexican population obtain factor loadings of less than .70 (Lasher & Faulkender, 1993;Sargent-Cox et al, 2013), values that according to Hair et al (2009) are not ideal, in the sense that the indicators (items) of a specific construct must converge or share a high proportion of common variance. While items 3 and 7 also present, both in the Mexican and non-Mexican Together with all the aforementioned, the results of the factorial invariance analyses between women and men; indicate a high congruence between pairs of factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to comment that of the eight items that were eliminated to achieve a better fit and greater discrimination capacity of the model proposed by Lasher and Faulkender,items 2,4,5,6 and 16 were also eliminated by Rivera-Ledesma et al (2007) and Ornelas, Gastélum, Lopez-Walle, et al (2016) in their studies on the factor structure of the Lasher and Faulkender's Anxiety about Aging Scale in a Mexican population, while these same items in other studies with a non-Mexican population obtain factor loadings of less than .70 (Lasher & Faulkender, 1993;Sargent-Cox et al, 2013), values that according to Hair et al (2009) are not ideal, in the sense that the indicators (items) of a specific construct must converge or share a high proportion of common variance. While items 3 and 7 also present, both in the Mexican and non-Mexican Together with all the aforementioned, the results of the factorial invariance analyses between women and men; indicate a high congruence between pairs of factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the Spanish-speaking population, there is limited research on the adaptation and validation of the questionnaire, which has shown adequate psychometric properties (Aguirre et al, 2017;Fernández-Jiménez et al, 2020;Ornelas, Gastélum, López-Walle, et al, 2016;Rivera-Ledesma et al, 2007;Zueck-Enríquez et al, 2021); however, these studies have evaluated the psychometric properties of the anxiety about aging questionnaire in older and younger adults. Lasher and Faulkender's (1993) Anxiety about Aging Scale (AAS) is based on the premise that anxiety about aging is an important factor in measuring attitudes and behaviors toward the elderly, as well as a mediating factor in the adaptation to the aging process itself; through the dimensions: physical, psychological, social and transpersonal or spiritual, the scale measures anxiety, worry, fear, fear or anticipation towards the various losses associated with aging.…”
Section: Introductionmentioning
confidence: 99%